THE EFFECTIVENESS OF USING WORD MAP TECHNIQUE IN TEACHING VOCABULARY AT THIRD GRADE STUDENTS OF IKIP MATARAM IN ACADEMIC YEAR 2015/2016 - Terasne, Terasne (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2017)
This research aims to find out the effectiveness of using ?Word Map? Technique in teaching vocabulary at third grades students of IKIP Mataram in academic year 2015/2016??. This was a quasi experimental research. The sample of this research was two classes, they were A class and B class in which consist of 39 students. It takes by using cluster random sampling. The sample of the research divided into two groups namely experimental group and control group. Experimental group was taught by Word Map Technique and control group was taught by Three Phase Technique. The design of the research as follow: Pre-test, Treatment, and Posttest.The instrument was multiple choices test consist of 25 items for right answers was  4 for each item. Then, for all right answer ranged 100 for the highest and for the lowest was 0. Based on the data analysis it was found that t-test score was 7.743 and t-table was 1.668. The result showed that the value of t-test was highest then the value of t-table. So, it conclude that there was significant effect of Word Map Technique in teaching vocabulary at third grades students of IKIP Mataram in academic year 2015/2016.